Distribution of components in epitaxial graded band gap heterostructures Cd(Mn, Zn)Te – Cd(Mn, Zn)HgTe and their photoelectrical properties - Vlasenko, O.I.; Babentsov, V.M.; Vlasenko, Z.K.; Ponedilok, A.V.; Kurilo, I.V.; Rudyj, I.O.; Kremenitskiy, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1998)
By using the method of VPE CdMnTe-CdMnHgTe, CdZnTe-CdZnHgTe heterocompositions were fabricated. Increase of their photo-sensitivity in comparison with the CdTe-CdHgTe structure is explained by removal of deformation stresses due to introduction of isovalent component (Mn, Zn) of smaller size and due to reduction of recombination activity of non-equilibrium charge carriers in the film. Photo-sensitivity increase in the field of metallurgical boundary in the CdMnTe-CdMnHgTe structure under increase of the Mn contents up to у Ј 0,08 in comparison to the CdZnTe-CdZnHgTe structure is connected with more precise matching of lattices matching of the initial materials. Other models of this phenomena are also discussed, conditioned in particular, by the influence of micro- and macro- heterogeneities of the diffusion interface, peculiarities of P-T diagrams, etc. On the basis of comparison of experimental and calculated profiles of the components distribution, the values of diffusion coefficient in the substrate and growing film were obtained. Методом ПФЕ одержані гетерокомпозиції CdMnTe-CdMnHgTe (КМТ-КМРТ), CdZnTe-CdZnHgTe (КЦТ-КЦРТ). Підвищення їх фоточутливості порівняно із структурою CdTe-CdHgTe (КТ-КРТ) пояснюється зняттям деформаційних напруг завдяки введенню ізовалентної складової (Mn, Zn) меншого розміру і зниженням рекомбінаційної активності нерівноважних носіїв заряду в плівці. Збільшення фоточутливості в області металургійної границі в структурі КМТ-КМРТ при збільшенні вмісту Mn до y Ј 0,08 порівняно із структурою КЦТ-КЦРТ пов.язується з більш прецизійним узгодженням параметрів кристалічних граток вихідних матеріалів. Обговорюються і інші моделі цих явищ, пов.язані, зокрема з впливом мікро- і макро неоднорідностей дифузійної границі, особливостями Р-Т-х діаграм і інш. На основі співставлення експериментальних і розрахункових профілів розподілу компонент отримані значення для їх коефіцієнтів дифузії в підкладці і наростаючій плівці. Методом ПФЭ получены гетерокомпозиции CdMnTe-CdMnHgTe, CdZnTe-CdZnHgTe. Повышение их фоточувствительности по сравнению со структурой CdMnTe-CdTe-CdHgTe объясняется снятием деформационных напряжений благодаря введению изовалентной составляющей (Mn, Zn) меньшего размера и снижением рекомбинационной активности неравновесных носителей заряда в пленке. Увеличение фоточувствительности в области металлургической границы в структуре CdMnTe-CdMnHgTe при увеличении содержания Mn до у Ј 0,08 по сравнению со структурой CdZnTe-CdZnHgTe связывается с более прецизионным согласованием параметров кристаллических решеток исходных материалов. Обсуждаются и другие модели этих явлений, обусловленные, в частности, влиянием микро- и макро неоднородностей диффузионной границы, особенностями Р-Т-х диаграмм и др. На основе сопоставления экспериментальных и расчетных профилей распределения компонент получены значения коэффициентов диффузии в подложке и нарастающей пленке.